Effect of surface chemistry on the dispersion and pH-responsiveness of chitin nanofibers/ natural rubber latex nanocomposites. (1st March 2019) - Yin, Jin; Hou, Jiarui; Huang, Shasha; Li, Na; Zhong, Ming; Zhang, Zejun; Geng, Yong; Ding, Beibei; Chen, Yuwei; Duan, Yongxin; Zhang, Jianming
Graphical abstract: Highlights: Carbonylated ChNFs have better dispersion than that of zwitterionic ChNFs in NRL. C-ChNFs/NRL nanocomposite films demonstrated obvious pH-responsiveness. NC-ChNFs/NRL nanocomposite films showed pH-stable mechanical properties. Abstract: Chitin nanofibers (ChNFs) have emerged as a rising nanomaterial due to their excellent mechanical properties, biocompatibility and biodegradability etc. Herein, carbonylated ChNFs (C-ChNFs) and zwitterionic ChNFs (NC-ChNFs) decorated with both amino (-NH2 ) and carboxyl (−COOH) groups were used to prepare ChNFs/natural rubber (NR) nanocomposite films by dip molding method, respectively. The results showed that C-ChNFs had better dispersion than that of NC-ChNFs in NRL matrix. Moreover, C-ChNFs/NR nanocomposite films demonstrated obvious pH-responsiveness owing to the association and disassociation of the hydrogen bonding between C-ChNFs under various pH conditions. In contrast, NC-ChNFs/NR nanocomposite films showed pH-stable mechanical properties because the protonation of -NH2 at pH < 7 and the ionization of −COOH at pH > 7 resulted in electrostatic repulsive force between NC-ChNFs. This study demonstrates that surface chemistry of ChNFs plays an important role on tailoring the performance of ChNFs/NRL nanocomposites.